Terrorism, Instability, and Democracy in Asia and Africa. - Cox, Dan G.; Falconer, John.; Stackhouse, Brian (Lebanon : Northeastern University Press, 2010)
A chilling, up-to-the-minute look at the links between political instability and terrorism in Asia and Africa.
Chapter 9: The Large and Constant Specter of Terrorism in South AsiaChapter 10: Central Asia and the Role of the Soviet Union; Chapter 11: Terrorism in Northern Africa; Chapter 12: The Terrorist Experience in Sub-Saharan Africa; Chapter 13: Conclusion and Policy Prescriptions; Index.
Print version record.
eBooks on EBSCOhost
Keywords: Political stability -- Asia; Terrorism -- Asia; Democracy -- Asia; Political stability -- Africa; Terrorism -- Africa; Democracy -- Africa; Asia -- Politics and government -- 21st century; Africa -- Politics and government -- 21st century; Stabilité politique -- Asie; Terrorisme -- Asie; Stabilité politique -- Afrique; Terrorisme -- Afrique; Asie -- Politique et gouvernement -- 21e siècle.; Afrique -- Politique et gouvernement -- 21e siècle.; LAW -- Constitutional; LAW -- Public; POLITICAL SCIENCE -- Political Freedom & Security -- Terrorism; Democracy; Politics and government; Political stability; Terrorism; Africa; Asia; 2000-2099